Pelaporan Posyandu Lansia Puskesmas Banguntapan III: Perancangan Sistem Informasi Berbasis Web - Hendra Rohman; Elmy Agnia (Indonesian of Health Information Management Journal (INOHIM), 2019)
AbstractPuskesmas Banguntapan III was the only one that has a working area with one subdistrict that oversees 16 elderly integrated services post. Each integrated services post sends the results of its activities every month to Puskesmas Banguntapan III. Reporting used to use microsoft excel was still found deficiencies, namely inconsistent data, delays in collecting reports, misplaced data, access rights used by all parties, and duplicate data. The aim to design a-based elderly integrated services post reporting information system web at Puskesmas Banguntapan III, especially for elderly patients. The method for developing-based information systems for elderly integrated services post reporting web using the system development life cycle (SDLC). Elderly integrated services post reporting information system displays the patient menu, report printing, graphic printing, backup data, restore data and settings. The results can help organize elderly integrated services post on registration, and make reports as needed sent to the Bantul District Health Office. This information system can facilitate elderly integrated services post cadres in carrying out input data and making reports. Keyword: elderly, integrated services post cadres, electronic medical record AbstrakPuskesmas Banguntapan III merupakan satu-satunya yang memiliki wilayah kerja dengan satu kelurahan yang membawahi 16 posyandu lansia. Setiap posyandu mengirimkan hasil kegiatannya setiap satu bulan ke Puskesmas Banguntapan III. Pelaporan yang digunakan menggunakan microsoft excel yang masih ditemukan kekurangan yaitu data tidak konsisten, keterlambatan pengumpulan pelaporan, salah simpan data, hak akses digunakan semua pihak, dan duplikat data. Tujuannya membuat perancangan sistem informasi pelaporan posyandu lansia berbasis web di Puskesmas Banguntapan III khususnya untuk pasien lansia. Metode pengembangan sistem informasi pelaporan posyandu lansia berbasis web menggunakan system development life cycle (SDLC). Pada sistem informasi pelaporan posyandu lansia ini menampilkan menu pasien, cetak laporan, cetak grafik, backup data, restore data dan pengaturan. Hasilnya dapat membantu penyelenggaraan posyandu lansia pada registerasi, dan pembuatan pelaporan sesuai kebutuhan yang dikirimkan ke Dinas Kesehatan Kabupaten Bantul. Sistem informasi ini dapat memudahkan kader posyandu lansia dalam melaksanakan input data dan membuat laporan.Kata Kunci: lansia, kader posyandu, rekam medis elektronik